Explore BrainMass

# Recurrence relations, compound interest, polynomials, number of combinations, & iteration

Not what you're looking for? Search our solutions OR ask your own Custom question.

This content was COPIED from BrainMass.com - View the original, and get the already-completed solution here!

Please help with the following discrete math involving recurrence relations, compound interest, polynomials, number of combinations and iteration.

14. Individual membership fees at the evergreen tennis club were \$50 in 1970 and have increased by \$2 per year since then. Write a recurrence relation and initial conditions for the membership fee n years after 1970

2. Prove by mathematical induction that 4(2n) +3 is a solution to the recurrence relation sn = 2sn-1 -3 for n ≥ 1 with the initial condition s0 = 7

https://brainmass.com/math/recurrence-relation/recurrence-relations-compound-interest-polynomials-339106

## SOLUTION This solution is FREE courtesy of BrainMass!

Please see the attached file for the solution in a Word Doc.

Discrete Math: Recurrence relations, compound interest, polynomials, number of combinations, & iteration

14. Individual membership fees at the evergreen tennis club were \$50 in 1970 and have increased by \$2 per year since then. Write a recurrence relation and initial conditions for the membership fee n years after 1970

For one year, \$50+\$2
For two years \$50+\$4
For three years \$50+\$6
For four years \$50+\$8
Forwarding like this, we can see that fee for n years after 1970, is given by =\$50+\$2n
2. Prove by mathematical induction that 4(2n) +3 is a solution to the recurrence relation sn = 2sn-1 -3 for n ≥ 1 with the initial condition s0 = 7
We have sn =4(2n) +3, sn-1 =4(2n-1) +3
So, 2sn-1 -3=2[4(2n-1) +3]-3=4(2.2n-1) +3=4(2n) +3= sn.
So, sn=4(2n) +3, with s0=4+3=7 is the solution for the recurrence relation

Alternate method
Given that sn = 2sn-1 -3
Put fn = sn-1 -3. This means s0 = 7 implies f1 = s0 -3=4.
Hence the given relation can be written as sn-3 = 2sn-1 -6=2(sn-1 -3)
This implies fn =2fn-1
Clearly f1, f2, f3 ...form a G.P. with first term 4 and common ratio 2. So, fn =4.2n-1
Hence we have fn+1 = sn -3=4.2n.
This gives sn =4.2n+3

This content was COPIED from BrainMass.com - View the original, and get the already-completed solution here!